Generic competences for end-of-degree projects in teacher education: students' and university teachers' perceptions - Eva González-Ortega; Ramiro Durán-Martínez (Ediciones Universidad de Salamanca, 2024)
The aim of this study is to analyse the perception of students and university teachers on the level of importance of generic competences when devising the End-of-Degree Project in Teacher Education, as well as on the amount of training the students receive regarding these competences. It also looks for possible differences between both groups and both ratings. An online survey was applied to a sample of 52 university teachers and 199 fourth year and graduate students of Primary/Preschool Teacher Degree courses. Participants were asked to rate 33 generic competences of an instrumental, interpersonal and systemic nature. It was found that the students thought they had received less training regarding many of the competences, as compared to the perception of university teachers. In addition, importance score was significantly higher than those related to training for both students and university teachers. These results highlight the need to explicitly address and assess the development of generic competences across all subjects in ways that meet the students' needs.